A high-shielding, corrosion-resistant cable and preparation method thereof
By using carbon fiber-loaded nano-nickel oxide materials in polyvinyl chloride cables, the problem of lack of electromagnetic shielding in traditional cables is solved, efficient electromagnetic wave absorption and loss is achieved, and the signal transmission and energy delivery stability of the cable is improved.
Patent Information
- Application Number
- CN202410790218.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-19
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-06-19
AI Technical Summary
Traditional polyvinyl chloride cable sheaths lack electromagnetic shielding performance and cannot effectively resist electromagnetic interference, affecting the stability of signal transmission and energy transmission.
Using carbon fiber-loaded nano nickel oxide polyvinyl chloride material, the coordination and pre-oxidation carbonization process of Ni2+ in imidazole catechol modified polyacrylonitrile fibers is uniformly dispersed in the carbon fiber to form an efficient electromagnetic shielding material.
The electromagnetic shielding performance of polyvinyl chloride cables is significantly improved. Through the effects of dielectric loss and magnetic loss, the cable absorbs and loses electromagnetic waves more effectively, and enhances the stability of signal transmission and energy delivery.
Smart Images

Figure CN118620337B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electromagnetic shielding, and in particular to a high-shielding and corrosion-resistant cable and a preparation method thereof. Background Art
[0002] In recent years, with the development of microwave technology, electromagnetic radiation on the ground has increased significantly, and excessive electromagnetic radiation has caused electromagnetic pollution. It is of great significance to develop electromagnetic shielding materials with light weight, large absorption bandwidth and high absorption intensity.
[0003] Due to its good comprehensive properties, polyvinyl chloride has a wide application in cable sheath materials. In products in civil and commercial fields, a large number of cables are needed to transmit signals and energy. However, when the cables are subject to electromagnetic interference, it will affect the stability of signal transmission and energy transmission. Therefore, it is necessary to develop cable materials with high electromagnetic shielding.
[0004] Carbon fiber is fibrous in appearance, soft and tough, has good processability, and has properties such as high temperature resistance, friction resistance, and corrosion resistance. It can be used as a reinforcing material and composited with resins, metals, ceramics, and carbon to manufacture high-performance advanced composite materials. In addition, carbon fiber can be used as a resonant electric dipole to form impedance matching characteristics with matrices such as nano-nickel oxide, magnetic materials, etc., showing a unique electromagnetic shielding effect. It is a very promising absorbing material. How to effectively load nano-nickel oxide into the carbon fiber matrix to form good impedance matching characteristics and achieve efficient electromagnetic shielding effect is a research difficulty. Summary of the invention
[0005] The invention prepares a polyvinyl chloride material containing carbon fiber loaded nano nickel oxide, solves the problem that traditional polyvinyl chloride cable sheath materials do not have the electromagnetic shielding function, and expands the application of polyvinyl chloride in high electromagnetic shielding cables.
[0006] The technical solution of the present invention is:
[0007] A method for preparing a high-shielding and corrosion-resistant cable material, the cable comprising a cable material cable layer, the cable material cable layer comprising raw materials in the following weight ratio: 2-12% carbon fiber loaded nano nickel oxide absorber, 0.1-0.5% antioxidant, 2-8% EPDM rubber, 18-25% epoxy soybean oil, 2-3% stabilizer, and 100% polyvinyl chloride;
[0008] The preparation method of cable material cable layer is as follows:
[0009] S1: Add imidazole catechol modified polyacrylonitrile to N,N-dimethylformamide, stir evenly to prepare polyacrylonitrile solution, then add nickel nitrate ethanol solution, ultrasonically oscillate for 1-2 hours, stir for 12-24 hours, and concentrate under reduced pressure to remove ethanol. Pour the solution into a syringe and spin it through an electrospinning machine at a voltage of 12-18 kV and a flow rate of 0.4-0.7 mL / h to obtain polyacrylonitrile loaded with nickel ions.
[0010] S2: Pre-oxidize the polyacrylonitrile loaded with nickel ions in an atmosphere furnace, and then carbonize it to obtain a carbon fiber loaded with nano nickel oxide absorber.
[0011] S3: extrude polyvinyl chloride, carbon fiber loaded with nano nickel oxide absorber, antioxidant, EPDM rubber, epoxy soybean oil and stabilizer into granules in a twin-screw extruder, and then form them by extruder to obtain a high-shielding and corrosion-resistant cable material layer.
[0012] Furthermore, the mass fraction of the polyacrylonitrile solution in S1 is 10-15%; the mass fraction of the nickel nitrate ethanol solution is 1-3%.
[0013] Furthermore, the volume usage of the nickel nitrate ethanol solution is 15-50% of the polyacrylonitrile solution.
[0014] Furthermore, the pre-oxidation process is in the air range, at a heating rate of 30°C / min, from room temperature to 280°C, and kept warm for 1 hour; the carbonization process is in a nitrogen atmosphere, at a heating rate of 20°C / min, to 800°C, and kept warm for 2 hours.
[0015] Furthermore, the temperature of zones 1-4 of the twin-screw extruder is 170-210°C, and the temperature of the die head is 210°C.
[0016] Furthermore, the preparation method of the imidazole catechol modified polyacrylonitrile is as follows:
[0017] S11: Add dichloromethane, 4-imidazolecarboxaldehyde, acryloyl chloride and N,N-diisopropylethylamine to a reaction flask, stir and react at room temperature for 4-10 hours, concentrate, wash with petroleum ether, dry, add the intermediate and dopamine to ethanol, condense and reflux at 70-85°C for 10-20 hours, cool, concentrate, separate the crude product by column chromatography, and use a solution of petroleum ether and ethyl acetate as eluent to obtain an ethylene imidazole catechol intermediate;
[0018] S12: Add dimethyl sulfoxide, acrylonitrile, vinyl imidazole catechol intermediate and azobisisobutyronitrile into a reaction bottle, carry out polymerization reaction under nitrogen protection, cool and pour the solution into water to precipitate, filter by suction, wash the filter cake with water and ethanol to obtain imidazole catechol modified polyacrylonitrile.
[0019] Furthermore, the molar amount of the alkenyl imidazole catechol intermediate is 5-30% of acrylonitrile.
[0020] Furthermore, the polymerization reaction is carried out at a temperature of 65-75° C. for 3-6 hours.
[0021] The beneficial technical effect of the present invention is that the present invention utilizes the polymerization of vinyl imidazole catechol intermediate and acrylonitrile to obtain imidazole catechol modified polyacrylonitrile, which contains catechol and imidazole functional groups, which can react with Ni 2+ To coordinate Ni 2+ Evenly distributed in the polyacrylonitrile fiber, during the pre-oxidation process, Ni 2+ Nano-nickel oxide is generated in situ in polyacrylonitrile fibers, and finally carbonized to obtain carbon fiber-loaded nano-nickel oxide absorbers.
[0022] The nano nickel oxide in the present invention is evenly dispersed in the carbon fiber, overcoming the agglomeration of the nano nickel oxide. The nano nickel oxide and the carbon fiber form a better interface polarization effect and impedance matching effect. As an absorber, the electromagnetic parameters and electromagnetic shielding performance of the cable layer of the polyvinyl chloride cable material are regulated. Through the dielectric loss and magnetic loss effects, the cable layer of the polyvinyl chloride cable material is more effectively absorbed and lost for electromagnetic waves. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a graph of electromagnetic wave reflection loss of the high shielding and corrosion resistant cable material prepared in the embodiment.
[0024] Figure 2 This is a graph of electromagnetic wave reflection loss of polyethylene cable material prepared in comparative example. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1
[0027] Add 30 mL of dichloromethane, 5 mmol of 4-imidazolecarboxaldehyde, 6 mmol of acryloyl chloride and 8 mmol of N,N-diisopropylethylamine to a reaction flask, stir and react at room temperature for 4 h, concentrate, wash with petroleum ether, dry, add the intermediate product and 5 mmol of dopamine to ethanol, condense and reflux at 85 ° C for 12 h, cool, concentrate, and separate the crude product by column chromatography, using a solution of petroleum ether and ethyl acetate as an eluent to obtain an ethylene imidazole catechol intermediate;
[0028] Add 250 mL of dimethyl sulfoxide, 40 mmol of acrylonitrile, 2 mmol of vinyl imidazole catechol intermediate and 0.3 mmol of azobisisobutyronitrile into a reaction bottle, carry out polymerization reaction at 75 ° C for 3 h under nitrogen protection, cool and pour the solution into water to precipitate, filter, wash the filter cake with water and ethanol to obtain imidazole catechol modified polyacrylonitrile.
[0029] Add imidazole catechol modified polyacrylonitrile to N,N-dimethylformamide, stir evenly to prepare 100 mL of 12% polyacrylonitrile solution, then add 15 mL of 2% nickel nitrate ethanol solution, ultrasonically vibrate for 1 hour, stir for 24 hours, and concentrate under reduced pressure to remove ethanol. Pour the solution into a syringe and spin it through an electrospinning machine at a voltage of 15 kV and a flow rate of 0.5 mL / h to obtain polyacrylonitrile loaded with nickel ions.
[0030] Polyacrylonitrile loaded with nickel ions was heated from room temperature to 280°C at a heating rate of 30°C / min in an atmosphere furnace in an air range, and kept warm for pre-oxidation for 1 hour; then, it was heated to 800°C at a heating rate of 20°C / min in a nitrogen atmosphere, kept warm and carbonized for 2 hours to obtain a carbon fiber loaded nano-nickel oxide absorber.
[0031] 100% of polyvinyl chloride, 2% of carbon fiber loaded nano nickel oxide absorber, 0.2% of antioxidant 168, 3% of EPDM rubber, 20% of epoxy soybean oil and 3% of calcium zinc stabilizer by weight are extruded and granulated in a twin-screw extruder, the temperatures of zones 1-4 are 170, 190, 200 and 210° C. respectively, the temperature of the die head is 210° C., and then the extruder is used for molding to obtain a high-shielding and corrosion-resistant cable material layer.
[0032] Example 2
[0033] Add 300 mL of dimethyl sulfoxide, 40 mmol of acrylonitrile, 5 mmol of vinyl imidazole catechol intermediate (the same method as in Example 1) and 0.35 mmol of azobisisobutyronitrile to a reaction bottle, and carry out polymerization reaction at 75°C for 3 h under nitrogen protection. After cooling, pour the solution into water to precipitate, filter, and wash the filter cake with water and ethanol to obtain imidazole catechol-modified polyacrylonitrile.
[0034] Add imidazole catechol modified polyacrylonitrile to N,N-dimethylformamide, stir evenly to prepare 100 mL of 12% polyacrylonitrile solution, then add 25 mL of 2% nickel nitrate ethanol solution, ultrasonically vibrate for 1 hour, stir for 24 hours, and concentrate under reduced pressure to remove ethanol. Pour the solution into a syringe and spin it through an electrospinning machine at a voltage of 15 kV and a flow rate of 0.5 mL / h to obtain polyacrylonitrile loaded with nickel ions.
[0035] Polyacrylonitrile loaded with nickel ions was heated from room temperature to 280°C at a heating rate of 30°C / min in an atmosphere furnace in an air range, and kept warm for pre-oxidation for 1 hour; then, it was heated to 800°C at a heating rate of 20°C / min in a nitrogen atmosphere, kept warm and carbonized for 2 hours to obtain a carbon fiber loaded nano-nickel oxide absorber.
[0036] 100% of polyvinyl chloride, 5% of carbon fiber loaded nano nickel oxide absorber, 0.2% of antioxidant 168, 3% of EPDM rubber, 20% of epoxy soybean oil and 3% of calcium zinc stabilizer by weight are extruded and granulated in a twin-screw extruder, the temperatures of zones 1-4 are 170, 190, 200 and 210° C. respectively, the temperature of the die head is 210° C., and then the extruder is used for molding to obtain a high-shielding and corrosion-resistant cable material layer.
[0037] Example 3
[0038] Add 400 mL of dimethyl sulfoxide, 40 mmol of acrylonitrile, 10 mmol of vinyl imidazole catechol intermediate (the same method as in Example 1) and 0.4 mmol of azobisisobutyronitrile to a reaction bottle, and carry out polymerization reaction at 70°C for 6 h under nitrogen protection. After cooling, pour the solution into water to precipitate, filter, and wash the filter cake with water and ethanol to obtain imidazole catechol-modified polyacrylonitrile.
[0039] Add imidazole catechol modified polyacrylonitrile to N,N-dimethylformamide, stir evenly to prepare 100 mL of 12% polyacrylonitrile solution, then add 40 mL of 2% nickel nitrate ethanol solution, ultrasonically vibrate for 1 hour, stir for 24 hours, and concentrate under reduced pressure to remove ethanol. Pour the solution into a syringe and spin it through an electrospinning machine at a voltage of 15 kV and a flow rate of 0.5 mL / h to obtain polyacrylonitrile loaded with nickel ions.
[0040] Polyacrylonitrile loaded with nickel ions was heated from room temperature to 280°C at a heating rate of 30°C / min in an atmosphere furnace in an air range, and kept warm for pre-oxidation for 1 hour; then, it was heated to 800°C at a heating rate of 20°C / min in a nitrogen atmosphere, kept warm and carbonized for 2 hours to obtain a carbon fiber loaded nano-nickel oxide absorber.
[0041] 100% of polyvinyl chloride, 8% of carbon fiber loaded nano nickel oxide absorber, 0.2% of antioxidant 168, 3% of EPDM rubber, 20% of epoxy soybean oil and 3% of calcium zinc stabilizer by weight are extruded and granulated in a twin-screw extruder, the temperatures of zones 1-4 are 170, 190, 200 and 210° C. respectively, the temperature of the die head is 210° C., and then the extruder is used for molding to obtain a high-shielding and corrosion-resistant cable material layer.
[0042] Example 4
[0043] Add 400 mL of dimethyl sulfoxide, 40 mmol of acrylonitrile, 12 mmol of vinyl imidazole catechol intermediate (the same method as in Example 1) and 0.4 mmol of azobisisobutyronitrile into a reaction bottle, and carry out polymerization reaction at 75 ° C for 3 h under nitrogen protection. After cooling, pour the solution into water to precipitate, filter, and wash the filter cake with water and ethanol to obtain imidazole catechol modified polyacrylonitrile.
[0044] Add imidazole catechol modified polyacrylonitrile to N,N-dimethylformamide, stir evenly to prepare 100 mL of 12% polyacrylonitrile solution, then add 50 mL of 2% nickel nitrate ethanol solution, ultrasonically vibrate for 1 hour, stir for 24 hours, and concentrate under reduced pressure to remove ethanol. Pour the solution into a syringe and spin it through an electrospinning machine at a voltage of 15 kV and a flow rate of 0.5 mL / h to obtain polyacrylonitrile loaded with nickel ions.
[0045] Polyacrylonitrile loaded with nickel ions was heated from room temperature to 280°C at a heating rate of 30°C / min in an atmosphere furnace in an air range, and kept warm for pre-oxidation for 1 hour; then, it was heated to 800°C at a heating rate of 20°C / min in a nitrogen atmosphere, kept warm and carbonized for 2 hours to obtain a carbon fiber loaded nano-nickel oxide absorber.
[0046] The weight ratio of 100% polyvinyl chloride, 12% carbon fiber loaded nano nickel oxide absorber, 0.2% antioxidant 168, 3% EPDM rubber, 20% epoxy soybean oil, and 3% calcium zinc stabilizer is extruded and granulated in a twin-screw extruder, the temperatures of zones 1-4 are 170, 190, 200, and 210° C., the temperature of the die head is 210° C., and then the extruder is used for molding to obtain a high-shielding and corrosion-resistant cable material layer.
[0047] The difference between Comparative Example 1 and Example 1 is that ordinary nano-nickel oxide is used instead of carbon fiber to load the nano-nickel oxide absorber.
[0048] Specifically, 100% polyvinyl chloride, 2% nano nickel oxide, 0.2% antioxidant 168, 3% EPDM rubber, 20% epoxy soybean oil and 3% calcium zinc stabilizer are extruded and granulated in a twin-screw extruder, the temperatures of zones 1-4 are 170, 190, 200 and 210°C respectively, the temperature of the die head is 210°C, and then the extruder is used for molding to obtain the cable layer of polyvinyl chloride cable material.
[0049] The difference between Comparative Example 2 and Example 1 is that polyacrylonitrile carbon fiber is used instead of carbon fiber to load the nano nickel oxide absorber.
[0050] Specifically, imidazole catechol modified polyacrylonitrile (the same as in Example 1) was heated from room temperature to 280°C in an atmosphere furnace in an air range at a heating rate of 30°C / min, and kept warm for pre-oxidation for 1 hour; then, in a nitrogen atmosphere, the temperature was increased to 800°C at a heating rate of 20°C / min, kept warm and carbonized for 2 hours to obtain polyacrylonitrile carbon fiber.
[0051] 100% of polyvinyl chloride, 2% of polyacrylonitrile carbon fiber, 0.2% of antioxidant 168, 3% of EPDM rubber, 20% of epoxy soybean oil and 3% of calcium zinc stabilizer by weight are extruded and granulated in a twin-screw extruder, the temperatures of zones 1-4 are 170, 190, 200 and 210° C. respectively, the temperature of the die head is 210° C., and then the extruder is used for molding to obtain a cable layer of polyvinyl chloride cable material.
[0052] The difference between Comparative Example 3 and Example 1 is that when preparing polyacrylonitrile, no vinyl imidazole catechol intermediate is added, and ordinary polyacrylonitrile is obtained.
[0053] Specifically, 400 mL of dimethyl sulfoxide, 40 mmol of acrylonitrile, and 0.4 mmol of azobisisobutyronitrile were added to a reaction bottle, and the polymerization reaction was carried out at 75°C for 3 hours under nitrogen protection. The solution was cooled and poured into water to precipitate, and the precipitate was filtered, and the filter cake was washed with water and ethanol to obtain polyacrylonitrile.
[0054] Add polyacrylonitrile to N,N-dimethylformamide, stir evenly to prepare 100 mL of 12% polyacrylonitrile solution, then add 50 mL of 2% nickel nitrate ethanol solution, ultrasonically oscillate for 1 hour, stir for 24 hours, and concentrate under reduced pressure to remove ethanol. Pour the solution into a syringe and spin it through an electrospinning machine at a voltage of 15 kV and a flow rate of 0.5 mL / h to obtain polyacrylonitrile loaded with nickel ions.
[0055] Polyacrylonitrile loaded with nickel ions was heated from room temperature to 280°C at a heating rate of 30°C / min in an atmosphere furnace in an air range, and kept warm for pre-oxidation for 1 hour; then, it was heated to 800°C at a heating rate of 20°C / min in a nitrogen atmosphere, kept warm and carbonized for 2 hours to obtain a carbon fiber loaded nano-nickel oxide absorber.
[0056] 100% of polyvinyl chloride, 12% of carbon fiber loaded nano nickel oxide absorber, 0.2% of antioxidant 168, 3% of EPDM rubber, 20% of epoxy soybean oil and 3% of calcium zinc stabilizer by weight are extruded and granulated in a twin-screw extruder, the temperatures of zones 1-4 are 170, 190, 200 and 210° C. respectively, the temperature of the die head is 210° C., and then the extruder is used for molding to obtain a cable layer of polyvinyl chloride cable material.
[0057] The cable materials prepared in each embodiment and comparative example were pressed into a ring with an inner diameter of 3 mm, an outer diameter of 8 mm, and a thickness of 3 mm. The electromagnetic parameters of the ring were tested using a vector network analyzer. The test frequency was 2-18 GHz. The test results are shown in the attached manual. Figure 1 and attached Figure 2 shown.
[0058] Attached to the instruction manual Figure 1 It is shown that in Example 3, when the weight ratio of carbon fiber loaded nano nickel oxide absorber is 8%, the prepared high shielding and corrosion resistant cable material has the best absorbing performance, and when the absorption frequency band is 10-12Hz, the maximum reflection loss is -29.8dB.
[0059] In Example 4, when the weight ratio of the carbon fiber loaded nano nickel oxide absorber is 12%, the maximum reflection loss is -25.1 dB when the absorption frequency band is 9-11 Hz.
[0060] In Example 1, when the weight ratio of the carbon fiber loaded nano nickel oxide absorber is 2%, the maximum reflection loss is -23.4 dB in the absorption frequency band of 9-11 Hz.
[0061] The cable materials prepared in the examples all showed excellent electromagnetic wave reflection loss performance. This is because the imidazole catechol-modified polyacrylonitrile contains catechol and imidazole functional groups, which can react with Ni 2+To coordinate Ni 2+ Evenly distributed in the polyacrylonitrile fiber, during the pre-oxidation process, Ni 2+ Nano-nickel oxide is generated in situ in polyacrylonitrile fiber, and finally carbonized to obtain carbon fiber loaded nano-nickel oxide absorber, so that the nano-nickel oxide is evenly dispersed in the carbon fiber, overcoming the agglomeration of nano-nickel oxide. Nano-nickel oxide and carbon fiber form better interface polarization and impedance matching effect. As an absorber, through the effects of dielectric loss and magnetic loss, the cable layer of polyvinyl chloride cable material can absorb and reduce the loss of electromagnetic waves more effectively.
[0062] Attached to the instruction manual Figure 2 It shows that comparative example 1 uses nano-nickel oxide instead of carbon fiber to load nano-nickel oxide absorber, which cannot form an impedance matching effect with carbon fiber. The reflection loss of the cable layer of polyvinyl chloride cable material to electromagnetic waves is poor. When the absorption frequency band is 11-13Hz, the maximum reflection loss is only -12.9dB.
[0063] Comparative Example 2 uses polyacrylonitrile carbon fiber instead of carbon fiber to load nano-nickel oxide absorber, which cannot form an impedance matching effect with nano-nickel oxide. The reflection loss of the cable layer of the polyvinyl chloride cable material to electromagnetic waves is poor. When the absorption frequency band is 8-10Hz, the maximum reflection loss is only -13.4dB.
[0064] Comparative Example 3: Unmodified polyacrylonitrile and Ni 2+ Compounding without Ni 2+ The coordination effect is formed, making Ni 2+ It cannot be evenly dispersed in the polyacrylonitrile matrix. After pre-oxidation and carbonization, the generated nano nickel oxide is not evenly loaded into the carbon fiber matrix. The impedance matching effect between the two is poor. The reflection loss of the cable layer of the polyvinyl chloride cable material to electromagnetic waves is not high. When the absorption frequency band is 8-10Hz, the maximum reflection loss is only -16.9dB.
[0065] The reflection losses of Comparative Examples 1-3 are all lower than that of Example 1.
[0066] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a highly shielded and corrosion-resistant cable, characterized in that: The high-shielding and corrosion-resistant cable comprises a cable material layer, which comprises the following raw materials in weight ratio: 2-12% carbon fiber loaded nano nickel oxide absorber, 0.1-0.5% antioxidant, 2-8% EPDM rubber, 18-25% epoxy soybean oil, 2-3% stabilizer, and 100% polyvinyl chloride; The preparation method of the cable material cable layer is as follows: S1: Add imidazole catechol modified polyacrylonitrile to N,N-dimethylformamide, stir evenly to prepare polyacrylonitrile solution, then add nickel nitrate ethanol solution, ultrasonically vibrate for 1-2h, stir for 12-24h, and concentrate under reduced pressure to remove ethanol. Pour the solution into a syringe and spin it through an electrospinning machine at a voltage of 12-18kV and a flow rate of 0.4-0.7mL / h to obtain polyacrylonitrile loaded with nickel ions; S2: pre-oxidizing the polyacrylonitrile loaded with nickel ions in an atmosphere furnace, and then carbonizing it to obtain a carbon fiber loaded with nano nickel oxide absorber; S3: extruding polyvinyl chloride, carbon fiber loaded with nano nickel oxide absorber, antioxidant, EPDM rubber, epoxy soybean oil, stabilizer in a twin-screw extruder to form pellets, and then extruder molding to obtain a high-shielding and corrosion-resistant cable material cable layer; The preparation method of the imidazole catechol modified polyacrylonitrile is as follows: S11: Add dichloromethane, 4-imidazolecarboxaldehyde, acryloyl chloride and N,N-diisopropylethylamine to a reaction flask, stir and react at room temperature for 4-10 hours, concentrate, wash with petroleum ether, and after drying, add the intermediate and dopamine to ethanol, condense and reflux at a temperature of 70-85°C for 10-20 hours, cool, concentrate, and separate the crude product by column chromatography, using a solution of petroleum ether and ethyl acetate as an eluent to obtain an ethylene imidazole catechol intermediate; S12: Add dimethyl sulfoxide, acrylonitrile, vinyl imidazole catechol intermediate and azobisisobutyronitrile into a reaction bottle, carry out polymerization reaction under nitrogen protection, cool and pour the solution into water to precipitate, filter by suction, wash the filter cake with water and ethanol to obtain imidazole catechol modified polyacrylonitrile.
2. The method for preparing a highly shielded, corrosion-resistant cable according to claim 1, characterized in that: The mass fraction of the polyacrylonitrile solution in S1 is 10-15%; the mass fraction of the nickel nitrate ethanol solution is 1-3%.
3. The method for preparing a highly shielded, corrosion-resistant cable according to claim 2, characterized in that: The volume usage of the nickel nitrate ethanol solution is 15-50% of the polyacrylonitrile solution.
4. The method for preparing a highly shielded and corrosion-resistant cable according to claim 1, characterized in that: The pre-oxidation process is to heat up from room temperature to 280°C at a heating rate of 30°C / min in air and keep it warm for 1 hour; the carbonization process is to heat up to 800°C at a heating rate of 20°C / min in nitrogen atmosphere and keep it warm for 2 hours.
5. The method for preparing a highly shielded and corrosion-resistant cable according to claim 1, characterized in that: The temperature of the twin-screw extruder zones 1-4 is 170-210°C, and the die temperature is 210°C.
6. The method for preparing a highly shielded and corrosion-resistant cable according to claim 1, characterized in that: The molar amount of the alkenyl imidazole catechol intermediate is 5-30% of acrylonitrile.
7. The method for preparing a highly shielded and corrosion-resistant cable according to claim 1, characterized in that: The polymerization reaction is carried out at a temperature of 65-75° C. for 3-6 hours.
Citation Information
Patent Citations
Imidazole side chain half-metallocene imine ligand, and method and application thereof
CN102659682A
Polyacrylonitrile fiber loaded cobalt-nickel alloy composite oxygen reduction catalytic material and preparation method thereof
CN113991130A